ANALISIS PUTUSAN LEPAS DARI TUNTUTAN HUKUM TERHADAP PELAKU TINDAK PIDANA - Mansyur Mansyur; Muhammad Gofar Harahap (Fakultas Hukum Universitas Borneo Tarakan, 2021)
AbstractThe phenomenon that has occurred in Indonesia is the determination of mental disorders which procedurally do not meet the elements of only looking at the physical condition of the perpetrators of criminal acts. This research was conducted based on how the procedure in determining a person has a mental disorder according to criminal procedural law, Is the decision of the Simalungun District Court Judge Number: 207/Pid.B/2015/Pn.Sim in accordance with the criminal procedure law in dealing with defendants with mental disorders. To find out the procedure for dealing with criminals who are suspected of having mental disorders in terms of proving and applying certainty to the perpetrators and knowing the considerations in the decisions discussed in imposing the release of perpetrators with mental disorders. This research method is the type of juridical and normative research, approach to the problem of sources of legal materials, techniques of collecting legal materials, analysis of legal materials. Conclusion The decision of the Simalungun District Court Number 207/Pid.B/2015/Pn.Sim, in determining the mental state of the defendant is only based on the judge's belief so that it is not bound by the procedures intended by criminal procedural law by involving expert witnesses, to prove the mental state of the defendant. where the psychiatrist should have a very important role in the trial considering the limited capabilities possessed by a judge in terms of mental health.Keywords: Release Decision, Lawsuits, Criminal Actors